The weight of the nation [videorecording (DVD)] (HBO Home Box Office ; Distributed by Warner Home Video, 2012)
"CONSEQUENCES examines the scope of the obesity epidemic and explores the serious health consequences of being overweight or obese. CHOICES offers viewers the skinny on fat, revealing what science has shown about how to lose weight, maintain weight loss and prevent weight gain. CHILDREN IN CRISIS documents the damage obesity is doing to our nation's children. Through individual stories, this film describes how the strong forces at work in our society are causing children to consume too many calories and expend too little energy; tackling subjects from school lunches to the decline of physical education, the demise of school recess and the marketing of unhealthy food to children. CHALLENGES examines the major driving forces causing the obesity epidemic, including agriculture, economics, evolutionary biology, food marketing, racial and socioeconomic disparities, physical inactivity, American food culture, and the strong influence of the food and beverage industry."--Producers.